Six Motivations for Students to Take Tutoring - Febriani, Afifah; Miftahurrahmah, Miftahurrahmah; Pajaria, Suci Ade; Nurhaliza, Siti (International Journal of Multidisciplinary Research of Higher Education, 2020)
Students who choose to take part in tutoring provide an indication of their various motivations and needs in their educational journey. That's exactly why this research aims to determine the motivation of students to take part in tutoring. This research used a qualitative method with a phenomenological approach, the data source was taken from ten informants consisting of three elementary school level students and seven junior high school level students. All interview data was then analyzed thematically using Miles and Huberman. Research findings showed six motivations for students to take tutoring, namely i) self-encouragement, ii) encouragement from parents, iii) following friends, iv) teacher recommendations, v) so that they can easily understand mathematics lessons vi) The learning process at school is not optimal. The results of this research can be used as initial data for future researchers by examining different issues related to this problem as well as various other issues relevant to this context.